2005
DOI: 10.1128/cdli.12.5.586-592.2005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Human Serum Immunoglobulin G againstO-Acetyl-Positive andO-Acetyl-Negative Serogroup W135 Meningococcal Capsular Polysaccharide

Abstract: The capsular polysaccharide of Neisseria meningitidis serogroup W135 is expressed in both O-acetyl-positive (OA ؉ ) and O-acetyl-negative (OA ؊ ) forms. This study investigates the impact of OA status (OA ؉ versus OA ؊ ) on serological measurements of anti-W135 immunoglobulin G (IgG) antibodies in immunized adults. W135-specific serum antibody assignments were made for 28 postimmunization sera from adults by enzyme-linked immunosorbent assay using the meningococcal standard reference serum CDC1992. The establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The above also holds true for capsular group Y, and a further potential factor is that the polysaccharide capsules for both groups Y and W135 can be in either an O-acetylated or de-O-acetylated form (20). For group W135, O-acetylation status was shown to impact serological measurements of antibodies directed against W135 in sera from immunized adults (15).…”
Section: Fig 2 Percentage Of Individuals With Rsba Titers Of ն8 Againmentioning
confidence: 99%
“…The above also holds true for capsular group Y, and a further potential factor is that the polysaccharide capsules for both groups Y and W135 can be in either an O-acetylated or de-O-acetylated form (20). For group W135, O-acetylation status was shown to impact serological measurements of antibodies directed against W135 in sera from immunized adults (15).…”
Section: Fig 2 Percentage Of Individuals With Rsba Titers Of ն8 Againmentioning
confidence: 99%
“…Nevertheless, for some sera, the agreement in anti-O-acetyl positive versus O-acetyl negative MenW IgG assignment was serum-specific and did not reflect the functional activity in vitro. 149 An original study in mice demonstrated that MenW CPS conjugates displaying low O-acetylation levels were more immunogenic than the plain CPS and that hydrazine-mediated reduction of the O-5 acetyl groups in the MenW CPS had no adverse effect on immunogenicity nor on the CPS structure as detected by NMR.…”
mentioning
confidence: 99%
“…The lack of O acetylation can contribute to a change in the antigenic structure of the capsular polymer, making it nonreactive with the anti-15B antibodies. O acetylation has been shown to be an important parameter when measuring functional antibody activity in meningococcus (2,10). With meningococcus groups C and Y, the O acetylation masks the epitopes on the Ps backbone to which functional antibody is directed (8).…”
mentioning
confidence: 99%